Cloning, Expression, Re-folding, and Purification of Protein Flic (salmonella Enteritidis) with Deletion of Amino Acids 220-320 - Anh, Nguyen Viet; Chau, Tran Thi Bao; Hoan, Nguyen Phuoc Khai; Hieu, Tran Van (VNU Journal of Science: Natural Sciences and Technology, 2022)
In order to develop high-performance subunit vaccines, many studies are currently aiming at the development of immunoadjuvants. Flagellin protein (FliC) contained in the Salmonella’s filament is one of the potential candidates for this purpose. However, the high antigenic property of FliC has made it difficult to apply for many vaccines.  A variant with the deletion of amino acids from 220 to 320 of flagellin has been proven to have an adjuvant effect with lower immunogenicity. In this present study, we cloned and expressed FliC D220-320 recombinant in Escherichia coli system. The expression of FliC Δ220-320 was induced by IPTG and confirmed by SDS-PAGE and Western Blot probed with 6xHis tag antibody. Results showed that most of the expressed protein is insoluble. The targeted protein was then solubilized, re-folded and purified by affinity chromatography method with the purity of 80 %. With these results, we successfully expressed FliC D220-320 recombinant protein and this is a source for the evaluation and development of immune adjuvants.